Design of a smart microgrid with small-scale hydro generation: a practical case study - Leite, Vicente (2022)
Microgrids are local electric grids integrating distributed generation and consumption, energy storage and management and power control. They can be an alternative for the energy supply of a house, a building, a small village or a wider region. Small-scale hydropower, in the range of 5 kW, consists of distributed generation systems gaining increasing interest. These so-called pico-hydro systems are becoming popular since they can take advantage of the integration of low-power wind generators and photovoltaic (PV) inverters, which are widely available at competitive prices. Thus, pico-hydro systems are not only relevant for energy generation in off-grid systems in remote areas but also for new contexts where the utility grid is available. This paper presents the design of a smart microgrid with small-scale hydro generation. It is a practical case study with the integration of two grid-connected pico-hydro turbines: a low-head propeller turbine and a water wheel. The microgrid was designed and implemented in a small museum: Casa da Seda (House of Silk). The energy generation is based on the complementarity between hydro and PV. The microgrid can operate in both grid-connected and islanded modes and feeds the House of Silk loads. The connection of both pico-hydro turbines into the microgrid is based on the integration of wind generators and PV inverters.